PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2008 – 2017 (STUDI KASUS PADA PT. TELEKOMUNIKASI INDONESIA TBK, PT. INDOSAT TBK, DAN PT. XL AXIATA TBK) - Lahallo, Fensca Fenolisa (Buletin Studi Ekonomi, 2019)
The purpose of this study is to compare the financial performance of PT. Telekomunikasi Indonesia Tbk, PT. Indosat Tbk, and PT. XL Axiata Tbk Period 2008 - 2017. This type of research is comparative research. The population used is the telecommunications service companies listed as public companies (issued) on the Indonesia Stock Exchange (IDX) for the period 2008 - 2017 and the sampling technique used is purposive sampling based on certain criteria and determined by companies that included into the classter 3 of the largest and best telecommunication companies in the period 2008 - 2017 and has published the annual financial statements in the year 2008 -2017. Thus the sample in this study is PT. Telekomunikasi Indonesia Tbk, PT Indosat Tbk and PT. PT.XL Axiata Tbk. Data analysis technique used was quantitative descriptive analysis and comparison test used statistical analysis (parametric statistical difference test). The results showed that from the results of different test using One-way ANOVA obtained results there are significant differences between financial performance of PT. Telekomunikasi Indonesia Tbk, PT. Indosat Tbk and PT. XL Axiata Tbk seen from liquidity ratios, solvency ratios, activity ratios and profitability ratios.